2010
DOI: 10.1126/science.1177801
|View full text |Cite
|
Sign up to set email alerts
|

Gene Doping and Sport

Abstract: Advances in gene therapy set the stage for the next generation of illegal doping, and doping detection, in sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
0
18
0
7
Order By: Relevance
“…Also, if a cell producing the desired product is infected by another virus, this could lead to overexpression of the protein 12 30. Expression is controllable by an inducer drug (eg, doxycycline, which is approved for human use), but since this is detectable, it is less likely to be used for gene doping 18 47

Storage and usage

Gene therapy would require good storage and it is questionable whether those wishing to abuse it are knowledgeable about proper handling procedures 41.

…”
Section: From Gene Therapy To Gene Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, if a cell producing the desired product is infected by another virus, this could lead to overexpression of the protein 12 30. Expression is controllable by an inducer drug (eg, doxycycline, which is approved for human use), but since this is detectable, it is less likely to be used for gene doping 18 47

Storage and usage

Gene therapy would require good storage and it is questionable whether those wishing to abuse it are knowledgeable about proper handling procedures 41.

…”
Section: From Gene Therapy To Gene Dopingmentioning
confidence: 99%
“…Though a couple of gene therapy products have been marketed outside China to date, at least 1843 gene therapy trials have been conducted worldwide with thousands of patients suffering from cancer diseases, cardiovascular and neurological diseases and a range of other diseases 10 15 19 34. Early clinical trials in Europe and the USA had limited results and even fatalities were reported from gene therapy;9 46 47 however, examples of successful gene therapy include treatment of SCID-X1 and Leber's congenital amaurosis 17. The proof of concept of various transfer strategies in gene therapy shows that we are at least at the beginning of a gene therapy revolution for patients with monogenic diseases 16 17 48…”
Section: From Gene Therapy To Gene Dopingmentioning
confidence: 99%
“…The successful development of gene therapy has provided the concepts, tools, opportunity and, in some cases, the justification for genetic modification of functions that affect normal human aspects, including athletic performance (Friedmann, 2010;Friedmann et al, 2010). The potential misuse of this type of therapy is regarded as gene doping.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, doping and cheating in sports were enabled by advances in pharmacology and physiology. Now, advances in molecular genetics have given rise to the potential to improve various non-medical human features including sports performance by the use of GM technology (3,4).…”
Section: Introductionmentioning
confidence: 99%